FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN SEKTOR PROPERTI - Lydia Sumiyati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
This researh aims to analyze about how is the influence of the financial performance of thecompany that is focused to the Price Earning Ratio (PER), Earning Per Share (EPS) and Return onAsset (ROA) toward the stock price in the company property period 2008 − 2012.The companies in this researh are BSDE (Bumi Serpong Damai Tbk), PWON (PakuwonJati Tbk), and ASRI (Alam Sutera Realty Tbk)) and taken by certain criteria which are the most liquidproperty companies (the frequency of occurrence of selling − buying shares) registered in theIndonesia Stock Exchange and included in the list of company IDX30. The methods of analysis thatwere used in this research by using F Test, T Test, Coefficient Determinants, and Linear RegressionTest.The results showed that PER, EPS, and ROA had significant influence toward stock prices.For PER had a positive influence but not significant influence towards stock prices, and EPS had asignificant positive influence towards stock prices, and ROA had a significant influence and negativeinfluence toward the company's stock price property sector